Pengembangan Aplikasi E-Commerce Mobile Produk Daur Ulang dengan Integrasi Jejak Transparansi Material - Muhammad Rafly Dwi Gunawan; Apriade Voutama (TIN: Terapan Informatika Nusantara, 2026)
Urban waste management in Indonesia faces supply chain transparency challenges, where consumers of recycled products generally cannot verify the origin of materials claimed as recycled. Based on the literature review, existing recycled product e-commerce platforms remain predominantly web-based and have not integrated cross-actor material tracking mechanisms within a single mobile ecosystem. This study designed and implemented SitesCraft, a mobile e-commerce application for recycled products with a Material Transparency Trail feature. The main contribution of this research is the integration of a mechanism that links waste purchase receipts from suppliers with product material-origin information accessible to consumers. The case study was conducted in Bekasi City, considering its characteristics as a densely populated satellite city with high waste generation volumes. The system was developed using the Waterfall method with a Backend-as-a-Service architecture and tested through Blackbox Testing on 16 test scenarios and usability evaluation using the System Usability Scale (SUS) with 10 respondents. Functional testing results showed 15 out of 16 scenarios met specifications (93.75%), with one scenario related to offline condition handling identified as inadequate. The SUS score of 76.75 placed the system in the Acceptable category (Grade B), with per item analysis identifying weaknesses in initial learning load due to multi-role feature complexity. The main limitation of this study includes material trail validation that still relies on digital input without independent physical verification.